"My God, here is the skull of a murderer!" Physical appearance and violent crime. Issue 2 (3rd April 2021) - Berveling, Jaco
ABSTRACT: Over the centuries, people have tried to determine character traits from a person's appearance, beginning with the physiognomic efforts of the Greek philosophers Socrates (ca. 470–399 bce ) and Aristotle (384–322 bce ) and still continuing today. In this quest, the discovery of criminal tendencies from someone's face always received special attention. This was also an important issue for physician Franz Joseph Gall (1758–1828). Gall maintained that a criminal's skull had a different shape than that of a law-abiding person. Phrenologists, as well as criminologists, including Cesare Lombroso (1835–1909), further propagated Gall's ideas and investigated countless heads of violent and petty criminals. This line of investigation led to much discussion and criticism. Were Gall, the phrenologists who followed him, and Lombroso sufficiently objective? Were these men really onto something, or were they led by prejudices? After Lombroso's time, physiognomy and cranioscopy were discredited. However, in the last decades, some researchers are again trying to find out whether people are indeed able to distinguish violent criminals from nonviolent criminals on the basis of their faces.